Early Blood Gas Predictors of Bronchopulmonary Dysplasia in Extremely Low Gestational Age Newborns. (14th May 2014) - Sriram, Sudhir; Condie, Joy; Schreiber, Michael D.; Batton, Daniel G.; Shah, Bhavesh; Bose, Carl; Laughon, Matthew; Van Marter, Linda J.; Allred, Elizabeth N.; Leviton, Alan
Abstract : Aim . To determine among infants born before the 28th week of gestation to what extent blood gas abnormalities during the first three postnatal days provide information about the risk of bronchopulmonary dysplasia (BPD). Methods . We studied the association of extreme quartiles of blood gas measurements (hypoxemia, hyperoxemia, hypocapnea, and hypercapnea) in the first three postnatal days, with bronchopulmonary dysplasia, among 906 newborns, using multivariable models adjusting for potential confounders. We approximated NIH criteria by classifying severity of BPD on the basis of the receipt of any O2 on postnatal day 28 and at 36 weeks PMA and assisted ventilation. Results . In models that did not adjust for ventilation, hypoxemia was associated with increased risk of severe BPD and very severe BPD, while infants who had hypercapnea were at increased risk of very severe BPD only. In contrast, infants who had hypocapnea were at reduced risk of severe BPD. Including ventilation for 14 or more days eliminated the associations with hypoxemia and with hypercapnea and made the decreased risk of very severe BPD statistically significant. Conclusions . Among ELGANs, recurrent/persistent blood gas abnormalities in the first three postnatal days convey information about the risk of severe and very severe BPD.